Arsenic exposure from drinking water and mortality from cardiovascular disease in Bangladesh: prospective cohort study. (5th May 2011) - Chen, Yu; Graziano, Joseph H; Parvez, Faruque; Liu, Mengling; Slavkovich, Vesna; Kalra, Tara; Argos, Maria; Islam, Tariqul; Ahmed, Alauddin; Rakibuz-Zaman, Muhammad; Hasan, Rabiul; Sarwar, Golam; et al.
Abstract : Objective To evaluate the association between arsenic exposure and mortality from cardiovascular disease and to assess whether cigarette smoking influences the association. Design Prospective cohort study with arsenic exposure measured in drinking water from wells and urine. Setting General population in Araihazar, Bangladesh. Participants 11 746 men and women who provided urine samples in 2000 and were followed up for an average of 6.6 years. Main outcome measure Death from cardiovascular disease. Results 198 people died from diseases of circulatory system, accounting for 43% of total mortality in the population. The mortality rate for cardiovascular disease was 214.3 per 100 000 person years in people drinking water containing <12.0 µg/L arsenic, compared with 271.1 per 100 000 person years in people drinking water with ≥12.0 µg/L arsenic. There was a dose-response relation between exposure to arsenic in well water assessed at baseline and mortality from ischaemic heart disease and other heart disease; the hazard ratios in increasing quarters of arsenic concentration in well water (0.1-12.0, 12.1-62.0, 62.1-148.0, and 148.1-864.0 µg/L) were 1.00 (reference), 1.22 (0.65 to 2.32), 1.35 (0.71 to 2.57), and 1.92 (1.07 to 3.43) (P=0.0019 for trend), respectively, after adjustment for potential confounders including age, sex, smoking status, educational attainment, body mass index (BMI), and changes in urinary arsenic concentration since baseline. Similar associations were observed when baseline total urinary arsenic was used as the exposure variable and for mortality from ischaemic heart disease specifically. The data indicate a significant synergistic interaction between arsenic exposure and cigarette smoking in mortality from ischaemic heart disease and other heart disease. In particular, the hazard ratio for the joint effect of a moderate level of arsenic exposure (middle third of well arsenic concentration 25.3-114.0 µg/L, mean 63.5 µg/L) and cigarette smoking on mortality from heart disease was greater than the sum of the hazard ratios associated with their individual effect (relative excess risk for interaction 1.56, 0.05 to 3.14; P=0.010). Conclusions Exposure to arsenic in drinking water is adversely associated with mortality from heart disease, especially among smokers.